Main Trends In Uzbekistan's Foreign Trade Relations With The Countries Of The Eurasian Economic Union - Gulyamova G.P (Genius Journals, 2025)
This article examines the key trends in the development of foreign trade relations between the Republic of Uzbekistan and the countries of the Eurasian Economic Union (EAEU). Drawing on statistical data and analytical reviews, it outlines the dynamics of trade turnover, the structure of exports and imports, and the role of individual EAEU member states - Russia, Kazakhstan, Belarus, and Kyrgyzstan - in shaping Uzbekistan’s foreign economic strategy. The study emphasizes the importance of Uzbekistan’s multivector approach to foreign economic policy and evaluates the potential benefits of deeper integration with the EAEU in the context of global challenges and regional transformation
Keywords: foreign trade; Eurasian Economic Union; export and import